Improving Speaking Competency of The Students at SMK N 4 Bangli Using Project-Based Learning - Dewi, Luh Putu Ayu Novita (Universitas Pendidikan Ganesha, 2017)
This study aimed at improving speaking competency of the students using project-based learning. The subjects of this study were the eleventh grade AP1 students of SMK Negeri 4 Bangli which consisted 25 students. The study was conducted by following the action research procedures and it was completed in two cycles. The result of the study showed that speaking competency of the students could be improved by using project-based learning. The result of post-test 2 proved that the students’ mean score was 80 which significantly improved from the pre-test result that was 69. The class percentage of the students passing the test was 100% which was beyond the expectation which was 75%. Based on the questionnaire, the students also had positive response towards the implementation of project-based learning. The result showed that learning English using project-based learning could improve their speaking competency in terms of fluency, pronunciation, grammar, and vocabulary.